Анализ применения систем виртуальной реальности - Жуковський, Є. А. (ХНУРЕ, 2019)
Virtual reality simulates both impact and reaction to impact. "That is, it is a kind of artificially created world with which a person can interact and receive a reciprocal reaction from it